Adaptation of the Evaluative Scale of Violent Behavior and Risk of Recidivism (SVVBRR) in a Peruvian penitentiary sample - Conde Mendoza, Jari Yasser (2018)
The judicial systems require psychologists to evaluate subjects who serve sentences in penitentiary establishments in order to assess the possibility of reinsertion in society. Consequently, prison psychologists have developed techniques and procedures for assessing the risk of violent behavior based on the identification of risk factors. The objective of this study was to adapt the first instrument for assessing the risk of violence in the Peruvian prison context. Content validity was evidenced by expert judgment and with a sample of 303 inmates, construct validity was identified through exploratory and confirmatory factor analysis. Finally, the diagnostic accuracy was established by means of the ROC curve. The results indicate that the adaptation of the EVCV-RR is an adequate instrument to assess the criminogenic risk.